2021
DOI: 10.1096/fj.202100224r
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary conserved olfactory receptor for foodborne and semiochemical alkylpyrazines

Abstract: Molecular recognition is a fundamental principle in biological systems. The olfactory detection of both food and predators via ecological relevant odorant cues are abilities of eminent evolutionary significance for many species. Pyrazines are such volatile cues, some of which act as both human‐centered key food odorants (KFOs) and semiochemicals. A pyrazine‐selective odorant receptor has been elusive. Here we screened 2,3,5‐trimethylpyrazine, a KFO and semiochemical, and 2,5‐dihydro‐2,4,5‐trimethylthiazoline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 97 publications
2
41
0
Order By: Relevance
“…Interestingly, in the screening of pyrazines, the mixture of isomers 2-ethyl-3,5(6)-dimethylpyrazine was found to activate OR5K1 with an EC50 of 21.18 μM. 50 In this work, we isolated the mixture and tested the individual isomers against OR5K1. We found that 2-ethyl-3,6-dimethylpyrazine (compound 2 ) has an EC 50 of 14.85 μM, while 2-ethyl-3,5-dimethylpyrazine (compound 13 ) could not be measured to saturation with the concentration range available.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, in the screening of pyrazines, the mixture of isomers 2-ethyl-3,5(6)-dimethylpyrazine was found to activate OR5K1 with an EC50 of 21.18 μM. 50 In this work, we isolated the mixture and tested the individual isomers against OR5K1. We found that 2-ethyl-3,6-dimethylpyrazine (compound 2 ) has an EC 50 of 14.85 μM, while 2-ethyl-3,5-dimethylpyrazine (compound 13 ) could not be measured to saturation with the concentration range available.…”
Section: Resultsmentioning
confidence: 99%
“…Most ORs are still orphan and the receptive range of a few ORs has been characterized until now. In this paper, we used the recently published ligand information on OR5K1 50 to model and refine the OR5K1 orthosteric binding site. We used a multi-template homology modeling approach, as previously suggested to be a successful strategy for OR modeling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations